2014
DOI: 10.1002/2013wr013687
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of SCHADEX extreme flood estimations to observed hydrometeorological variability

Abstract: [1] Stochastic flood simulation methods are typically based on a rainfall probabilistic model (used for simulating continuous rainfall series or for estimating probabilities of random rainfall events) and on a rainfall-runoff model. Usually, both of these models are calibrated over observed hydrometeorological series, which may be subject to significant variability and/or nonstationarity over time. The general aim of this study is thus to propose and test a methodology for performing a sensitivity analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…It has also been applied successfully in France (Garavaglia et al, 2011;Neppel et al, 2014), Austria and West Canada (Brigode et al, 2014). MEWP is a general model imposing no specific hypotheses on the data, so its application in other regions of the world is absolutely worth considering.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been applied successfully in France (Garavaglia et al, 2011;Neppel et al, 2014), Austria and West Canada (Brigode et al, 2014). MEWP is a general model imposing no specific hypotheses on the data, so its application in other regions of the world is absolutely worth considering.…”
Section: Discussionmentioning
confidence: 99%
“…MEWP is a general model imposing no specific hypotheses on the data, so its application in other regions of the world is absolutely worth considering. The only limitation is that a classification into weather patterns suitable for evaluating extreme precipitation is needed as a precursor to such an analysis, but this is already available in several regions around the world (see Brigode et al, 2014) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also shown that the soil saturation level is not as important in comparison with the parameters of the hydrological model. For example, Brigode et al (2014) tested the sensitivity of the SCHADEX model using a set of block bootstrap method. In each of these experiments, different sub-periods selected from the observation record were used in turn to calibrate the rainfall model, 20 the hydrological model and to determine the sensitivity to the soil saturation level.…”
mentioning
confidence: 99%
“…Although the mixture of distributions over weather patterns has revealed efficient in other countries (e.g. in Norway and Canada, Brigode et al, 2014;Blanchet et al, 2015), it might be less relevant in, e.g., monsoon climate regions where the consideration of seasons seems Figure 10. Map of the probability of daily rainfall to exceed 1mm and of the mean of nonzero rainfall in the three WPs of the season-at-risk.…”
mentioning
confidence: 99%